Seychelles : First Review under the Policy Coordination Instrument and Request for Modification of Targets. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
This paper discusses Seychelles' First Review Under the Policy Coordination Instrument (PCI) and Request for Modification of Targets. All quantitative targets for end-December 2017, the program's first review test date, were met. Although there are no structural reform targets due for the first review, the structural agenda for 2018 is proceeding in line with the program. Given the authorities' strong program implementation and continued commitment to safeguarding macroeconomic stability, the IMF staff supports the authorities' request for the completion of the first review under the PCI and the modification of the end-June 2018 and end-December 2018 quantitative targets for reserve money.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet